Lobachevskii Journal of Mathematics
http://ljm.ksu.ru
Vol. 14, 2004, 3–16
© A. Aljouiee
Abdulla Aljouiee
ON THE BRAUER MONOID OF
S3
(submitted by M. Arslanov)
ABSTRACT. In [HLS], the authors showed that the Brauer monoid of a finite
Galois group can be written as a disjoint union of smaller pieces (groups).
Each group can be computed following Stimets by defining a chain complex
and checking its exactness. However, this method is not so encouraging
because of the difficulty of dealing with such computations even with small
groups. Unfortunately, this is the only known method so far. This paper is to
apply Stimets’ method to some idempotent weak 2-cocycles defined on
S3. In
particular, the idempotent 2-cocycles whose associated graphs have two
generators. Some nice results appear in the theory of noncommutative
polynomials.
1. Preliminaries
Let K∕F
be a finite Galois extension of fields and let
G
be its Galois group. A weak 2–cocycle is a function
f : G × G → K
satisfying
- fσ(τ,ν)f(σ,τν) = f(στ,ν)f(σ,τ)
- f(σ, 1) = f(1,σ) = 1
for all σ,τ,ν ∈ G.
If we define an algebra Af
associated with f to be the
algebra generated as a K-vector
space by the indeterminates {xσ : σ ∈ G}
with the relations xσxτ = f(σ,τ)xστ
and xσk = kσx
σ
for k ∈ K,
x1 = 1, then
Af is
called a weak crossed product. Condition (i) above guarantees the associativity
of Af.
In the classical theory f
does not take the value 0,
and in that case Af is a
central simple F-algebra.
The set H = {σ ∈ G : f(σ,σ−1) ⁄= 0} is a subgroup
of G called the inertial
subgroup of f. We
define an order “≤”
on G∕H by
σH ≤ τH if and only if
f(σ,σ−1τ) ⁄= 0. This order is lower
subtractive, that is if σH ≤ τH
then σH ≤ αH ≤ τH if and
only if σ−1αH ≤ σ−1τH. In
this order, H
is the unique minimal element (root) and has the property
f(H × H) ⊆ K∗ [HLS]. The weak
crossed product Af
can be written as
Af = ⊕
σ∈HKxσ ⊕⊕
σ⁄∈HKxσ = B ⊕ J
where J = ⊕
σ∉HKxσ is the
radical of Af and
B = ⊕
σ∈HKxσ is a classical crossed
product algebra for f∣H×H.
In particular B is a
central simple KH–algebra.
Given a weak 2-cocycle f,
define a function e : G × G →{0, 1}
by e(σ,τ) = 0 if and
only if f(σ,τ) = 0.
Then e
is a weak 2-cocycle called the idempotent weak 2-cocycle associated to
f.
Two weak 2-cocycles f,g
are called cohomologous (or equivalent) if there is a function
α : G → K∗ such
that
f(σ,τ) = α(σ)ασ(τ)
α(στ) g(σ,τ) for all σ,τ ∈ G.
Any two cohomologous weak 2-cocycles have the same associated idempotent cocycle.
Under the equivalence relation introduced above the set of classes of weak 2-cocycles
from G × G to
K forms a monoid
denoted by M2(G,K).
The subgroup of invertible elements of this monoid is the usual cohomology
group H2(G,K∗).
Let e be an idempotent
weak 2-cocycle. If f is a weak
2-cocycle associated to e then
we can define a function g : G × G → K
by
g(σ,τ) = (f(σ,τ))−1if f(σ,τ) ⁄= 0
0 otherwise.
Then g is a weak
2-cocycle associated to e.
If [ ⋅]
denotes the equivalence class in the relation above, let
Me2(G,K) = {[f] ∈ M2(G,K) ∣ [f][e] = [f] and there is a
weak 2-cocycle g
such that [f][g] = [e]}. Then
Me2(G,K) is a group
with identity [e]
and M2(G,K) = ∪
eMe2(G,K)
(disjoint) where the union is over all idempotent weak
2-cocycles, [H1]. In a similar way, we can define the group
Mei(G,K) of
ith
dimension.
The set of all idempotent cocycles on
G × G with inertial
subgroup H
is in 1 − 1
correspondence with all lower subtractive orders (graphs) on
G∕H with unique root
H. Whenever we refer
to the graph for e,
we mean the graph associated to the weak 2-cocycle
e. If
[f] ∈ Me2(G,K) then
f and
e
have the same associated graph. The following results and
definitions are from [S1] and [S2]. Each idempotent 2-cocycle
e with trivial
inertial subgroup H
determines a ring Re = ℤ{xσ : σ ∈ G}∕Ie
where Ie is the ideal
generated by {xσxτ − xστ ∣ σ ≤ στ}. The ring
Re is called the derived
ring of e. To define
a graded Re–module,
it is more convenient to use the notation
gi for the elements
of the group G and
[g1 ,g2,…,gk] for the free generators
of the Re–module,
where gi ≤ gi+1
according to the relation defined above.
Define a graded Re–module
M by
M = ⊕
n∈ℤMn
where
Mn = ⊕
g1<⋯<gnRe[g1,…,gn]n ≥ 1,gi ⁄= 1
Re n = 0
ℤ n = −1
0 n ≤−2
with differentials dn[g1,…,gn] = xg1[g1−1g
2,…,g1−1g
n] + ∑
(−1)i[g
1,…,
g ̂ i,
…,
gn ]. We call the
pair (M,d) the chain
complex of e.
This definition can be given in a similar manner if
H ⁄= {1}. Suppose
f is a function
from Gn to
a field K
which satisfies
- in case
f(g1,g2,…,gi−1, 1,gi+1,…,gn) ⁄= 0,
we have f(g1,g2,…,gi−1, 1,
gi+1,…,gn) = 1
for all g1,g2,…,gn
in G
and all 1 ≤ i ≤ n,
- f(1, 1,…, 1,g, 1,…, 1) = 1
for all g ∈ G,
and
- for each g1,g2,…,gn+1
in G,
fg1
(g2,…,gn+1) ∏
i evenf(g1,…,gigi+1,…,gn+1)
= f(g1,…,gn) ∏
i oddf(g1,…,gigi+1,…,gn+1)
if n is
even, and
fg1
(g2,…,gn+1)f(g1,…,gn) ∏
i evenf(g1,…,gigi+1,…,gn+1)
= ∏
i oddf(g1,…,gigi+1,…,gn+1)
if n is odd. We
then call f a
weak n-cocycle.
The first condition is analogous to the standard degeneracy conditions used in
homological algebra, but still allows for the possibility that certain cochains
may take on non-invertible values.
The second condition ensures that the cochains (cocycles) have a sufficient
amount of invertibility.
If f is a weak
n-cocycle and there is
another weak n-cocycle
h and an invertible
cochain β : Gn−1 → K∗
such that f = ∂β ⋅ h,
where
∂β(g1,…,gn)
= βg1
(g2,…,gn)β(−1)n
(g1,…,gn−1) ∏
β(−1)i
(g1,…,gigi+1,…,gn),
then we say f is
cohomologous to h
and write f ∼ h. Let
Mn(G,K) be the monoid of weak
n-cocycles modulo the
equivalence relation ∼.
Then Mn(G,K)
is called the weak Galois cohomology monoid. The class of cocycles equivalent
(cohomologous) to the identity are known as weak coboundaries.
Since the groups Mei(G,K)
are components of the required monoid, we are interested in computing these
groups. Stimets ([S1],[S2]) has shown that under a sharp condition (exactness of
(M,d)) we have the following
isomorphism Mei(G,K) ≃ Ext
Rei(ℤ,K∗)
for all i, where
the groups ExtRei(ℤ,K∗)
are relatively easier to deal with because they are well known and
Re acts
on K∗ in
the obvious way. (See [S1],[S2] for details). In this paper, we investigate
exactness in some special cases. Exactness is always guaranteed at
M0
([S1]). It is quite difficult to check exactness in general but using
the “contraction process” makes the situation somewhat easier. If
g1 < ⋯ < gn, call
[g1 ,⋯,gn]
(n)–cell
in Mn.
Proposition 1.1 (Contraction process) (Stimets). Let Cn ∈ Mn,
Cn−1
∈ Mn−1
be two cells such that Cn
does not appear in the boundary of Mn+1
and in the boundary of an n-cell
not equal to Cn,
the cell Cn−1
does not appear. But if Cn−1
appears in the boundary of Cn,
then the chain complex (M′,d)
obtained by removing Cn
and Cn−1
is exact at Mn′
if and only if (M,d)
is exact at Mn.
Moreover, (M,d)
and (M′,d)
have the same homology groups.
This procedure allows us to cancel cells gradually until we reach a point
after which we cannot proceed any further. Then we can investigate exactness
at fewer modules.
2. Contracting to a Simpler Graph
In some cases, we can simplify the given graph to a smaller one. This section
is devoted to demonstrating a class of graphs that can be contracted to a specific
form of Z4
and showing that such graphs possess exact chain complex.
Lemma 2.1. In the ring R = ℤ{x,y}∕(x2 = y2),
if α(x − 1) = β(y − 1),
then α = h(x + 1),
β = h(y + 1)
for some h ∈ R.
Proof. We claim that the set V = {yɛxyxy…xyxi ∣ ɛ ∈{0, 1},
i ≥ 0} forms a
ℤ-basis for
R. Clearly
V generates
R. We show the
independence. Let M
be a free module on T = {Y ɛXY ⋯Y Xi ∣ ɛ ∈{0, 1},
i ≥ 0}. The module
M can be viewed
as a right R-module
by defining the action:
(Y ɛXY
1X⋯XY jXi) ⋅ x = Y ɛXY
1X⋯XY jXi+1
(Y ɛXY
1X⋯XY jXi) ⋅ y = Y ɛXY
1X⋯XY j+1Xi−1if i is odd
Y ɛXY
1X⋯XY j−1Xi+3if i is even.
This action is well-defined and notice that
(Y ɛXY
1X⋯XY jXi) ⋅ y2 = (Y ɛXY
1X⋯XY jXiy) ⋅ y
= Y ɛXY
1X⋯XY j+1Xi−1 ⋅ yif i is odd
Y ɛXY
1X⋯XY j−1Xi+3 ⋅ yif i is even
= (Y ɛXY
1X⋯XY jXY j+1 ⋅ y)Xi−1
Y ɛXY
1X⋯XY jXi+2
= Y ɛXY
1X⋯XY jXi+2
= (Y ɛXY
1X⋯XY jXi) ⋅ x2.
So we can define a homomorphism ϕ : R →
Endℤ(M)
by
ϕ(x) = right multiplication by x.
ϕ(y) = right multiplication by y.
Now, for zi ∈ V ,
if ∑
aizi = 0, then
ϕ(∑
aizi)(1) = 0 = ∑
aiZi⇒ai = 0 for all
i, and we
showed the claim. Now, we define a total order on the basis elements as follows: To
each yɛxy
1x⋯xyjxi ∈ V , assign
a degree (ɛ, 2, 2,…, 2︸ j, 1, 1,…, 1︸ i)
and let deg m = (1
2)
for all m ∈ ℤ∗,
deg0 = 0. If
u, v ∈ V , we define
u ≤ v if the length of the
corresponding tuple of v
is greater than the length of the corresponding tuple of
u. If
they have the same length, then compare the first numbers on the
right, if they are the same go to the next numbers and so on. Notice
that
ɛ, 2, 2,…, 2︸ j, 1, 1,…, 1︸ i ⋅ x = ɛ, 2, 2,…, 2︸ j, 1, 1,…, 1︸ i+1
and
ɛ, 2, 2,…, 2︸ j, 1, 1,…, 1︸ i⋅y = ɛ, 2, 2,…, 2︸ j−1, 1, 1,…, 1︸ i+3i is even
ɛ, 2, 2,…, 2︸ j+1, 1, 1,…, 1︸ i−1i is odd.
This shows that multiplying an element of
V by
x or
y
increases the degree. Since any monomial in
V ends from the
right with either y
or xi,
i > 0, we can write
any element in V
as a sum f + gy
where f and
g are sums of
monomials of V
ending with xi,
i > 0. We say
f is the component
of 1 and g is the
component of y.
Remember that in this form any term in the sum
g must end
with x1.
Let α = f1 + g1y,
β = h1 + k1y where
f1 ,g1h1 and
k1 are sums of
elements in V
which end with xi,
i > 0. Let
f, g,h and
k be of the largest
degrees in f1,g1,h1 and
k1 respectively.
The equation α(x − 1) = β(y − 1)
gives that
fx + gyx − gy + lower terms in both components
= kx2 − h + hy − ky + lower terms in both components. (2.1)
Let us denote by (g)
for the degree of g,
(g, 2, 1) for the degree
of gyx and
(k, 1, 1) for the degree of
kx2. From (2.1), if
we assume that g ⁄= 0,
and h ends
with x1,
we get
Case 1. If
(h) < (k)
then
(g) = (k)
and
(g, 2, 1) ≤ (k, 1, 1)
(impossible).
Case 2. If
(h) ≥ (k)
then
(g) = (h)
and
(g, 2, 1) ≤ max{(h), (k, 1, 1, )}
(impossible).
Now assume g ⁄= 0
and h ends
with xi,
i > 1. This
implies that g = k
and fx = hy. Let
∑
ℓ=0th
ℓ be the
component of 1 in β
where hℓ ends
with xi,
i > 1, for all
ℓ and
ht = h. Equation(2.1) implies
that there exists hj
for some j
such that gyx = hjy or
gyx = hj. The latter is clearly
impossible since hj
ends with xi,
i > 1. The first is also
impossible since hjy = hj′xiy = hj′yxi iis even
hj′xyxi−1iis odd ≥ 3,
and in both cases hjy
ends with xr,
r > 1. So,
gyx ⁄= hjy for
all j.
Thus g must
be 0 and either k = 0
or k = h. In the
first case, ∑
ℓ=0th
ℓ = β
where hℓ ends
with xi,
i > 1 for all
ℓ. Equation (2.1)
implies that fx = hy.
But hy always
ends with x2i.
so f ends
with x2i−1
and f = uyx2i−1 for
some u.
So h = ux2i
u′yx2i+1
.
Cancel fx
with hy
in (2.1) we get the term of the highest degree in the left hand side is
f, but
f = hℓy for any
ℓ. Therefore
f = h which is impossible.
This forces h = k.
Hence the original equation takes the form
f1 (x − 1) = h′(1 + y)(y − 1) where
h′
is the sum of either components. This implies that
f1 (x − 1) = h′(y2 − 1) = h′(x2 − 1) = h′(x + 1)(x − 1)⇒α = h′(x + 1) and
β = h′(y + 1).
□
Theorem 2.2. The chain complex of the idempotent weak 2-cocycle
e
whose graph is given by:
over ℤ4
is exact.
Proof. We have M0 = ℤ{x,y}∕(x2 = y2) = R,
M1 = R[1] ⊕ R[2] ⊕ R[3].
M2 = R[1, 2] ⊕ R[3, 2],
where x = x1,
y = x3.
We need to check the exactness of the following chain complex:
0→M2d2 →M1d1 →M0→0.
As stated earlier, we always have exactness at M0.
Now d2(α[1, 2] + β[3, 2]) = 0⇒α(x1[1] − [2] + [1]) + β(x3[3] − [2] + [3]) =
0⇒αx1 + α = 0,
−α − β = 0
and βx3 + β = 0⇒α = β = 0
and d2
is injective. To check exactness at M1,
let z = a[1] + b[2] + c[3] ∈ ker d1,
then z ∈imd2
if and only if z′ = z + d
2(b[1, 2]) = (a + bx1 + b)[1] + c[3] ∈imd2.
Let −s = a + bx1 + b.
Now, z′ ∈kerd
1⇒s(x1 − 1) = c(x3 − 1).
By the lemma above, the unique solution for such an equation is s = h(x1 + 1)
and c = h(x3 + 1)
for some h ∈ R.
So z′ = −h(x
1 + 1)[1] + h(x3 + 1)[3] = d2(−h[1, 2] + h[3, 2]).
Hence z ∈imd2,
so imd2 = kerd1.
□
Remark 2.3. We joint each weak 2-cocycle with a chain complex and a
unique graph, so excising cells in the complex is equivalent to cancelling
edges in the corresponding graph, and we are free to talk about one of
these two contractions instead of the other.
Corollary 2.4. Let e
be an idempotent weak 2-cocycle and let us denote by
Γe its lower subtractive
graph on a finite group G
with a derived ring ℤ{x,y}∕(x2 = y2).
If Γe
can be contracted to a graph of the form:
with σ2 = τ2 = ν, then the
chain complex of e
is exact.
Proof. This is a direct consequence of Theorem 2.2 and Proposition 1.1.
□
Example 2.1. Consider the idempotent
e
which is given by its graph over the quaternion group
Q =
{±1,±i,
±j,±k}:
It is easy to check that Re = ℤ{x,y}∕(x2 = y2)
where x = xi,
y = xj.
d3[i,k,−i] = xi[j,−1] − [k,−i] + [i,−i] − [i,k]
d3[j,−k,−j] = xj[i,−1] − [−k,−j] + [j,−j] − [j,−k]
The cells [i,k,−i]
and [j,−k,−j] can be
excised with [i,k]
and [−k,−j]
respectively. We now only have the relations:
d2[i,−1] = xi[i] − [−1] + [i]
d2[i,−i] = xi[−1] − [−i] + [i]
d2[j,−k] = xj[i] − [−k] + [j]
d2[j,−1] = xj[j] − [−1] + [j]
d2[j,−j] = xj[−1] − [−j] + [j]
d2[k,−i] = xk[j] − [−i] + [k]
Notice that the cells [k,−i],
[j, −j],
[j, −k] and
[i, −i] can be
excised with [k],
[−j],
[−k] and
[−i]
respectively. And then we are left with a graph of the form:
where i2 = j2 = −1. So, the
chain complex of e
is exact.
Corollary 2.5. In the previous example Mei(Q,K) ≃ Ext
Rei(ℤ,K∗)
where Q =
{±1,±i,±j,±k}
is the Galois group of the extension K∕F
for some base field F.
3. S3
with Two Generators
We will need some lemmas before we state and prove the main result in this
work.
Lemma 3.1. There is no non-trivial solution for the equation α(x − 1) = β(y − 1)
over the ring R = ℤ{x,y}∕(yx = xy2).
Proof. First, we show that the set {xiyj∣i,j ≥ 0}
forms a basis for R
over ℤ.
Let M
be the free ℤ–module
generated by {XiY j∣i,j ≥ 0}.
Define the following action to make M
a right R–module.
Xi Y jx = Xi+1Y 2j,
Xi Y jy = XiY j+1
for all i,j.
This action is well-defined as we have seen in Lemma 2.1 and we can define
a homomorphism ϕ : R → Endℤ(M)
by x↦
multiplication from the right by x,
y↦
multiplication from the right by y.
So, for any combination t = ∑
aijxiyj = 0,
we have ϕ(t)(1) = 0
or ∑
aijXiY j = 0
and hence aij = 0
for all i,j.
Let xsyt
be denoted by (s,t).
We define a degree function on the basis elements in R
by (s,t) < (s′,t′)
if s < s′.
If s = s′,
then (s,t) < (s′,t′)
if t < t′.
Notice that multiplying by x,y
from the right gives (s,t)x↦(s + 1, 2t),
(s, t)y↦(s,t + 1).
Let α = (s1,t1) + (s2,t2)+
lower degrees, where (s1,t1) > (s2,t2),
β = (s′,t′)+
lower degrees. α(x − 1) = β(y − 1)
gives that (s1 + 1, 2t1) − (s1,t1) + (s2 + 1, 2t2)+
lower degrees = (s′,t′ + 1) − (s′,t′)+
lower degrees ⇒(s1 + 1, 2t1) = (s′,t′ + 1),
that is, s′ = s
1 + 1
and t′ = 2t
1 − 1.
We claim that (s′,t′) > max{(s
1,t1),
(s2 + 1, 2t2)}.
Clearly s′ > s
1
since s′ = s
1 + 1.
s2 ≤ s1⇒s2 + 1 ≤ s′,
if s2 + 1 < s′,
we are done. So, let s2 + 1 = s′,
thus, s1 = s2.
This implies t1 > t2…
(*). Assume that t′ ≤ 2t
2,
so 2t1 − 1 ≤ 2t2
or t2 ≥ t1
which contradicts (*). □
Lemma 3.2. In the ring R = ℤ{x,y}∕(xyx = y2),
α(x − 1) = β(y − 1)
implies that α = k0(xn−1 + xn−2 + ⋯ + 1)(1 + xy)
and β = k0(1 − xn + (xn−1 + xn−2 + ⋯ + 1)y),
for any k0 ∈ R
and n ∈ ℕ.
Proof. Using an idea similar to what is in Lemma 3.1, we can show that
S = {yɛxi1yxi2y⋯yxiℓ,
ɛ ∈{0, 1},
ij , ℓ ∈ ℤ+
for j ⁄= ℓ,
iℓ ∈{0, 1,…}}
forms a ℤ-basis
for R.
Assign to each element yɛxi1yxi2y…yxiℓ
a degree (ɛ,i1,i2,…,iℓ)
if iℓ > 0
and (ɛ,i1,i2,…,iℓ−1)
for yɛxi2y…yxiℓ−1y.
If f
ends from the right with xi,
i > 0,
denote by (f)
for degree of f,
(f + k)
for fxk,
(f, 1)
for fyx.
Notice also that we can express any element in R
as f0 + g0y
where f0
and g0
are sums of monomials from S
ending with xi,
i > 0.
Call f0
the component of 1 and g0
the component of y.
Let f,g,h and
k be of the largest
degree in α,β
in both components. So
(f + gy + ⋯)(x − 1) = (h + ky + ⋯)(y − 1)
| (3.1) |
⇒fx + gyx − gy+ lower terms
= kxyx − h + hy − ky+ lower
terms ⇒
- (g) = (h − k)
- max((f + 1), (g, 1)) = max((k + 1, 1), (h)).
We discuss the following cases:
Case 1. If
g = 0
then
h = k
and
(f + 1) = (k + 1, 1)
(impossible).
Case 2. labelcs2.6 If
g ⁄= 0
and
(h) < (k)
then
(g) = (k)
and from (ii)
(f + 1) = (k + 1, 1)
(impossible).
Case 3. If g ⁄= 0
and (h) > (k) then
(g, 1) = (k + 1, 1)⇒g = mkx and
h = rkx for some
m, r ∈ ℤ∗. Substituting
in the equation (3.1)
yields m = 1 = −r and
so, g = kx = −h. Let
g′ , k′,h′ be of the next
largest degree (g′) < (g),
(k′ ) < (k),
(h′ ) < (h), then
we get
fx + kxyx + g′yx − kxy − g′y + lower terms
= −kxy + kx + h′y + kxyx − ky + k′xyx + lower terms⇒
(i)′
(g′ ) = (h′− k)
(ii)′
max((f + 1), (g′, 1)) = max((k + 1), (k′ + 1, 1)).
Again if g′ = 0
then since h′ = k = tfx,
t ∈ ℤ∗ and
equation (3.1)
gives fx+ lower
terms = tfx2+ lower
terms ⇒f = 0 and
hence h′ = k = f = g′ = g = h = 0.
If g′ ⁄= 0, then
(h′ ) ≤ (k)⇒(g′) = (k) and
hence (g′) = (k′ + 1)⇒g′ = sk = tk′x,
s, t ∈ ℤ∗. As above we
find s = t = 1. Repeat
this step to get gi = kix,
ki+1 = kix where
(ki+1) > (ki) and
equation (3.1)
becomes
(F +k0(xn+xn−1+⋯+x)y)(x−1) = (−k
0xn+H′+k
0(xn−1+⋯+1)y)(y−1)
| (3.2) |
where F is the sum
of components of 1
in α,
H′ the sum of
components of 1
in β that have
degrees less than h.
Let A := (xn−1 + ⋯ + 1), so
equation (3.2)
reads
(F + k0Axy)(x − 1) = (−k0xn + H′ + k
0Ay)(y − 1)⇒
Fx − F + k0Axyx − k0Axy
= H′y − H′ + k
0Axyx − k0xny − k
0Ay + k0xn⇒
Fx − F = H′y − H′− k
0y + k0xn
(since − xn − A = −Ax − 1)⇒
k0 = H′⇒
F(x − 1) = k0(xn − 1)⇒
F(x − 1) = k0(xn−1 + ⋯ + 1)(x − 1) = k
0A(x − 1)⇒
F = k0A.
Therefore
α(x − 1) = (k0A + k0Axy)(x − 1) = k0A(1 + xy)(x − 1)
| (3.3) |
and
β(y − 1) = (−k0xn + k
0 + k0Ay)(y − 1) = k0(−xn + 1 + Ay)(y − 1)
= k0(−xny + xn + y − 1 + Axyx − Ay)
= k0(−Axy − y + xn + y − 1 + Axyx)
(−xny − Ay = −Axy − y)
= k0((xn − 1) + Axy(x − 1))
= k0(A(x − 1) + Axy(x − 1))
= k0A(1 + xy)(x − 1) = α(x − 1).
□
Lemma 3.3. In the ring R = ℤ{x,y}∕(xyx = yxy),
the solutions of α(x − 1) = β(y − 1)
are α = h(xy − y + 1)
and β = h(yx − x + 1)
for some h ∈ R.
Proof. Since xyx = yxy
in R,
any element in R
can be written in a unique way as a combination of elements of the form
xi1 yj1xi2yj2…xiℓyjℓ
where i1,jℓ ≥ 0,
i2 , … ,iℓ−1 ≥ 2,
j1 , … jℓ−1 ≥ 1,
iℓ ≥ 2
if jℓ > 0
and iℓ ≥ 1
if jℓ = 0.
The form yxy
is always replaced by xyx.
This set of monomials forms a ℤ-basis
for R
by applying the same trick in Lemma 3.1. Assign to each such element
xi1 yj1xi2yj2…xiℓyjℓ
a degree (i1,j2,i2,j2,…,iℓ,jℓ)
and notice that
(i1,j1,i2,j2,…,iℓ,jℓ)x = (i1,j1,…,iℓ + 1, 0) if jℓ = 0
(i1,j1,…,iℓ,jℓ, 1, 0)if jℓ ⁄= 0
(n1, m1,…,mt−1,nt,mt)y =
= (n1,m1,…,nt,mt + 1) if mt ⁄= 0
(n1,m1,…,mt−1,nt, 1) if mt = 0 and nt > 1
(n1,m1,…,nt−1 + 1, 1,mt−1, 0)if mt = 0 and nt = 1
Obviously, these two terms can not be equal except if
mt = 0 and
nt = 1. If
jℓ = 0 then the
equality implies (h′xiℓ−1yxiℓ)x = (h′xiℓ−1−1yiℓ+1x)y
for some h′ ∈ R.
If jℓ ⁄= 0 then the
equality gives jℓ = mt−1 = 1
and iℓ = nt−1 + 1. So,
(h′′ xi1y)x = (h′′xiℓ−1yx)y for some
h′′ ∈ R. But in the first
case we note that h′xiℓ−1yxiℓ = h′xiℓ−1−1yiℓxy,
so in all cases if (i1,j1,i2,j2,…,iℓ,jℓ)x = (n1,m1,…,mt−1,nt,mt)y
then there is h ∈ R
such that hxy = (i1,j1,i2,j2,…,iℓ,jℓ),
hyx = (n1,m1,…,mt−1,nt,mt). Now,
let α = ∑
i=1rα
i,
β = ∑
i=1sβ
i, so by a suitable
rearrangement, α(x − 1) = β(y − 1)
implies that α1x = β1y⇒α1 = h1xy
and β1 = h1yx and
hence h1xyx−h1xy+α2x−α2+α3x−α3+⋯ = h1yxy−h1yx+β2y−β2+β3y−β3+…⇒α2x = −h1yx or
α2 = −h1y. Similarly,
we find β2 = −h1x,
α3 = h1,
β3 = h1,
α4 = h2xy,
β4 = h2yx,…⇒α = ∑
i=1qh
i(xy − y + 1) and
β = ∑
i=1qh
i(yx − x + 1) for some
integer q.
Take h = ∑
i=1qh
i.
□
Definition 3.1. Let e
be a weak 2-cocycle and let Γe
be its graph. Then, we call the elements of G
of level 1 generators of Γe.
That is the elements lie right above the root of Γe
are called generators.
Note that generators of the graph certainly generate the group itself.
Theorem 3.4. Let e
be an idempotent 2-cocycle whose graph has two generators over S3 = {σ,τ∣σ2τ = τσ,σ3 = τ2 = 1}.
Then e
admits an exact chain complex.
Proof. Using a computer program, it can be shown that there are nine
distinct lower subtractive graphs with two generators over S3.
Five of them are trees which admit exact graded modules (see [S2]). The
remaining four are:
By excising cells, we end up with
Mj i = 0
for all j > 2,
i = 1, 2, 3, 4. Let
0 → M2id2i
→M1id1i
→M0i → ℤ → 0 be the chain
complex of ei,
i = 1, 2, 3, 4,
which we get after excision. We always have exactness at
M0i. At
M2i, it is easy to show
that d2i is injective
for all i. To show
exactness at M13,
let z = a[σ2τ] + b[σ2] + c[σ] + d[στ] ∈ ker d
13, so
z ∈imd23 if and
only if z′ = z + d
23(c[σ2,σ] + d[σ2,στ]) = α[σ2τ] + β[σ2] ∈imd
23,
for some α,β ∈ R3.
But z ∈ ker d13⇒z′ ∈ ker d
13⇒α(x − 1) = β(y − 1)⇒ by
Lemma 3.1 α = β = 0.
Thus, z ∈imd23 if
and only if 0 ∈imd23
which is always true. A similar idea can be applied to show exactness at
M12. For
M14, let
u = p[σ2τ] + q[σ2] + r[τ] + s[στ] ∈ ker d
14, so
u ∈imd24 if and
only if u′ = γ[σ2τ] − δ[τ] ∈imd
24 for
some γ,δ ∈ Re4.
Since u′ ∈ ker d
14⇒ by
Lemma 3.3 γ = h(xy − y + 1),
δ = h(yx − x + 1) for some
h ∈ Re4⇒u ∈imd24 if and only
if u′ = h(xy − y + 1)[σ2τ] − h(yx − x + 1)[τ] ∈imd
24, but
clearly d24{h(1 − y)[σ2τ,σ2] + h[σ2,στ] − h[τ,στ]} = u′.
For M11, let
z = a[σ2τ] + b[σ2] + c[σ] + d[στ] ∈ ker d
11 ⇒ z ∈imd
21 if and
only if z′ = z + d
21(c[σ2,σ] + d[σ2,στ]) = α(σ2τ) − β[σ2] ∈imd
21 for
some α,β ∈ Re1.
Since z ∈ ker d11 ⇒ z′ ∈ ker d
11 and
α(x − 1) = β(x − 1) in the
ring ℤ{x,y}∕(xyx = y2) = R
e1. This
implies that α = k0(xn−1 + ⋯ + 1)(1 + xy),
β = k0(1 − xn + (xn−1 + ⋯ + 1)y) (by Lemma 3.2).
So z ∈imd21 if and
only if z′ = k
0A(1 + xy)[σ2τ] − k
0(1 − xn + Ay)[σ2] ∈imd
21.
Notice that 1 − xn = A − Ax.
So z′ ∈imd
21 if and
only if z′′ = k
0A((1 + xy)[σ2τ] − (1 − x + y)[σ2]) ∈imd
21.
But z′′ = d
21(x[σ2,στ] + [σ2τ,σ] − [σ2,σ]).
□
Corollary 3.5. For any idempotent weak 2-cocycle e
over S3
with two generators, Mei(S
3,K) ≈ExtRei(ℤ,K∗).
References
[A] A. Aljouiee, On Weak Crossed Products, Frobenius Algebras and Weak Bruhat
Ordering, J. Algebra, to appear.
[H1] D. Haile, On Crossed Product Algebras Arising from Weak Cocycles, J. Algebra,
74, 1982, 270-279.
[H2] D. Haile, The Brauer Monoid of a Field, J. Algebra, 81, 1983, 521-539.
[HLS] D. Haile, R. Larson, M. Sweedler, Almost Invertible Cohomology Theory and the
Classification of Idempotent Cohomology Classes and Algebras by Partially
Ordered Sets with a Galois Group Action, Amer. J. Math., 105, 1983, 689-814.
[S1] R. Stimets, Weak Galois Cohomology and Group Extension, Communications
in Algebra, 2000.
[S2] R. Stimets, Relative Weak Cohomology and Extension, J. Algebra, to appear.
TEACHERS COLLEGE, P.O. BOX 32644, RIYADH 11438, SAUDI ARABIA
E-mail address: joa111@lycos.com
Received December 12, 2003